2022
DOI: 10.1155/2022/5346563
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Serum Exosomal miRNAs as Diagnostic Biomarkers for Gastric Cancer Using Small RNA Sequencing

Abstract: Background/Aim. Exosomal miRNAs are promising tumor biomarkers. This research explored the diagnostic value of serum exosomal miRNAs by analyzing the exosomal miRNAs derived from the serum of gastric cancer patients. Methods. Deep sequencing of exosomal miRNAs was performed using an Illumina HiSeq2500 sequencer on serum samples from three healthy subjects in the normal control group (group N) and six gastric cancer patients in the gastric cancer treatment group (group T). Bioinformatics analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The mean sample size of groups of patients with GC was 98 (range, 23-386 patients), whereas the mean sample size of the control groups was 62 (range, 12-151 patients). A total of 26 studies analyzed the diagnostic value of RNAs for GC: MiRNAs in 13 studies (22,24,25,(28)(29)(30)(31)(32)(33)37,40,42,44,45), four of which performed validation tests (25,29,31,44); lncRNAs in nine studies (19,20,23,26,35,38,39,41,45); circular RNAs (circRNAs) in three studies (21,27,34); P-element induced wimpy testis-interacting RNAs (piRNAs) in one study (42); mRNA in one study (43); and a single study reported the diagnostic value of protein (36). A total of nine studies set a diagnostic cut-off value, which was determined using the Youden Index (19,23,27,31,33,34,39,41,45).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The mean sample size of groups of patients with GC was 98 (range, 23-386 patients), whereas the mean sample size of the control groups was 62 (range, 12-151 patients). A total of 26 studies analyzed the diagnostic value of RNAs for GC: MiRNAs in 13 studies (22,24,25,(28)(29)(30)(31)(32)(33)37,40,42,44,45), four of which performed validation tests (25,29,31,44); lncRNAs in nine studies (19,20,23,26,35,38,39,41,45); circular RNAs (circRNAs) in three studies (21,27,34); P-element induced wimpy testis-interacting RNAs (piRNAs) in one study (42); mRNA in one study (43); and a single study reported the diagnostic value of protein (36). A total of nine studies set a diagnostic cut-off value, which was determined using the Youden Index (19,23,27,31,33,34,39,41,45).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It was then discovered that the expression of miR-10401-3p, miR-1255b-5p, and miR-6736-5p in serum exosomes from GC patients was considerably lower than in serum exosomes from healthy people. Taken together, these data show that exosomal miR-10401-3p, miR-1255b-5p, and miR-6736-5p could be used as diagnostic biomarkers for GC [ 92 ]. Zhang et al also applied small RNA sequencing to uncover differentially regulated miRNAs using exosomes isolated from GC patient plasma as well as from healthy subjects.…”
Section: Exosomal Secretion From Cancer Cellsmentioning
confidence: 99%
“…Because of the heterogeneity of cancer cells, exosomal miRNAs from host cancer cells can activate the receptors or change miRNA or RNA expression in the neighboring cancer cells to alter their biological phenotypes. [12] Numerous publications present various exosomal miRNAs as potential biomarkers of breast cancer, [20] lung cancer, [21][22][23][24] gastric cancer, [25][26][27][28] colorectal cancer, [29][30][31][32] EC, [33] epithelial ovarian cancer, [34] and other cancers. [35][36][37][38][39][40][41][42][43][44][45] Here, as reported by Srivastava A etc, exosomes with a unique miRNA signature can be isolated from the urine of symptomatic women who are diagnosed with EC.…”
Section: Introductionmentioning
confidence: 99%